PENGARUH LINGKUNGAN KERJA, PENDIDIKAN DAN KEDISIPLINAN TERHADAP KINERJA PEGAWAI KANTOR CAMAT PELANGIRAN KABUPATEN INDRAGIRI HILIR - jurnalmap map; Adi Ahmad Putra; Hadi Susanto; Sutarji ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This study aims to analyze the environment, education and discipline on the performance of employees of the Pelangiran Sub-District Office of Indragiri Hilir Regency. By using cross tabulation data which was analyzed using multiple regression analysis tools, it can be seen that the R value above 50% is equal to 95.7%. The value of simultaneous determination (R square) is 0.916, which means that variations in work environment, education and discipline on the performance of employees of the Pelangiran Sub-District Office in Indragiri Hilir Regency changed 91.6% while the remaining 8.4% were produced by other variables that were not approved. In this study it can be seen that the variables of environmental motivation, education and discipline of participation together (simultaneous) on the performance of employees of the Pelangiran Sub-District Office of Indragiri Hilir Regency produce Fcount values ÔÇïÔÇïof 112.359 and Ftables of 2.911. By using the t test, it can be seen all the independent variables of work environment, education and discipline related to the performance of employees of the Pelangiran Sub-District Office of Indragiri Hilir Regency, while education is the most dominant variable compared to the employees of the Pelangiran Sub-District Office in Indragiri Hilir Regency. Keywords: work environment, education, discipline, performance